The Structural system of traditional Malay Dwellings in Sambas Town West Kalimantan, Indonesia - Zairin Zain, (Universiti Kebangsaan Malaysia, 2012)
The architecture of the Sambas traditional dwellings in West Kalimantan, Indonesia, one of the national heritage, has contributed particular characteristic structures. This study mainly focuses on these structural systems. A detailed investigation will be done on three type of Malay dwelling roof styles: Potong Limas (Limas style), Potong Kawat (Kawat style) and Potong Godang (Godang style). Analyzing the types of the structural systems used in the research objects, the author found an amazing endurance of these dwellings to toward the environmental conditions. This research is performed using the positivistic method and the data used were verified on the field and analyzed qualitatively. The utilization of local structures, such as the type of foundation, the wall construction and the roof slopes were built in unison with the nature